2011
DOI: 10.1111/j.1095-8312.2011.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics and biogeography of the Balkan ‘sand gobies’ (Teleostei: Gobiidae): vulnerable species in need of taxonomic revision

Abstract: Within the Atlantic-Mediterranean region, the 'sand gobies' are abundant and widespread, and play an important role in marine, brackish, and freshwater ecosystems. They include the smallest European freshwater fish, Economidichthys trichonis, which is threatened by habitat loss and pollution, as are several other sand gobies. Key to good conservation management is an accurate account of the number of evolutionary significant units. Nevertheless, many taxonomic and evolutionary questions remain unresolved withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
4
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 110 publications
8
54
4
19
Order By: Relevance
“…Other serious taxonomic issues include the tiny sand gobies of Western Greece. For example, recent genetic work has provided new evidence that Knipowitschia populations from various water bodies of the western coast of Greece may be conspecific with Knipowitschia milleri, previously thought to occur only in the lower part of the Acheron River (Vanhove et al, 2011b). Bearing in mind that few Ionian Knipowitschia populations are adequately studied morphologically, and that much phenotypic variation is observed in the Knipowitschia generally (Kovačić, 2005(Kovačić, , 2008, it is uncertain whether the morphological features of the Acheron K. milleri represent distinctive identification attributes.…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
“…Other serious taxonomic issues include the tiny sand gobies of Western Greece. For example, recent genetic work has provided new evidence that Knipowitschia populations from various water bodies of the western coast of Greece may be conspecific with Knipowitschia milleri, previously thought to occur only in the lower part of the Acheron River (Vanhove et al, 2011b). Bearing in mind that few Ionian Knipowitschia populations are adequately studied morphologically, and that much phenotypic variation is observed in the Knipowitschia generally (Kovačić, 2005(Kovačić, , 2008, it is uncertain whether the morphological features of the Acheron K. milleri represent distinctive identification attributes.…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
“…1) has only existed for ß4500 years (Westman and Sohlenius 1999), there are several species that exhibit characteristics of local adaptation in this area (Johannesson and André 2006;Johannesson et al 2011), including the sand goby (Pomatoschistus minutus) (Pallas) (Larmuseau et al 2010(Larmuseau et al , 2009a(Larmuseau et al , 2009b. Several closely related species have, however, entered and speciated in freshwater in the Balkan region (Vanhove et al 2012). S1) is widely distributed and inhabits the shores of the Mediterranean Sea, the North East Atlantic, and the Baltic Sea including the very low salinity waters in the Gulf of Bothnia, but it has not been found in freshwaters (Kullander et al 2012).…”
mentioning
confidence: 99%
“…P. microps and P. minutus belong to two different clades of the 'sand goby group' radiation. The divergence time of the two clades is estimated to be 2-5 Mya (Huyse et al 2004;Vanhove et al 2012) and behaviors including sound may have diverged during this time, and hence show a phylogenetic signal (Malavasi et al 2012). The two other sympatric 'sand goby group' species in shallow bays of Sweden (Kullander et al 2012), Gobiusculus flavescens (Fabricius, 1779) and P. pictus, as well as the deep water species Pomatoschistus norvegicus (Collett, 1902), appear to belong to the same clade as P. minutus.…”
Section: Discussionmentioning
confidence: 99%
“…The two other sympatric 'sand goby group' species in shallow bays of Sweden (Kullander et al 2012), Gobiusculus flavescens (Fabricius, 1779) and P. pictus, as well as the deep water species Pomatoschistus norvegicus (Collett, 1902), appear to belong to the same clade as P. minutus. P. marmoratus, the sister species to P. microps (Huyse et al 2004;Vanhove et al 2012), is not found in Sweden (Kullander et al 2012). G. flavescens, which is semipelagic and not benthic, is at present not in the genus Pomatoschistus, rendering it paraphyletic and in need of revision (Vanhove et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation